Comparison of Indoor Localization Systems Based on Wireless Communications - Dalce, Rejane; Val, Thierry; Bossche, Adrien V. (Scientific Research Publishing, 2011)
Localization using a Wireless Sensor Network (WSN) has become a field of interest for researchers in the past years. This information is expected to aid in routing, systems maintenance and health monitoring. For example, many projects aiming to monitor the elderly at home include a personal area network (PAN) which can provide current location of the patient to the medical staff. This article presents an overview of the current trends in this domain. We introduce the mathematical tools used to determine position then we introduce a selection of range-free and range-based proposals. Finally, we provide a comparison of these techniques and suggest possible areas of improvement.
Keywords: Wireless Sensor Networks (WSNs); Localization; Range-Based; Range-Free